2021
DOI: 10.7759/cureus.12949
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Degeneration or Sagittal Balance With Modic Changes in the Cervical Spine

Abstract: Objective: This study evaluates the relationship between degenerative and Modic changes (MCs) in the cervical spine and compares the results with the cervical sagittal balance parameters.Methods: We retrospectively reviewed 275 patients with neck pain who applied to our outpatient clinic and underwent cervical magnetic resonance imaging (MRI) and cervical anteroposterior (AP)/lateral (Lat) X-ray radiography between January 2016 and January 2018. The clinics, demographic information, and radiological findings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…First, we included participants aged 10-19. This age range can be regarded as wide, considering that the sagittal alignment of the spine changes as a child grows and the amount of smartphone usage varies significantly with age [20][21][22][23][24][25][26][27]. For the same reason, the age of the participants has been suggested to be the most critical confounding factor in related studies [13].…”
Section: Discussionmentioning
confidence: 99%
“…First, we included participants aged 10-19. This age range can be regarded as wide, considering that the sagittal alignment of the spine changes as a child grows and the amount of smartphone usage varies significantly with age [20][21][22][23][24][25][26][27]. For the same reason, the age of the participants has been suggested to be the most critical confounding factor in related studies [13].…”
Section: Discussionmentioning
confidence: 99%
“…The sagittal parameters of cervical spine are important parameters to reflect the mechanics of cervical spine and the mechanical stress in the sagittal plane of vertebral body and are important basis for evaluating the clinical status of patients and predicting the prognosis of diseases [10]. Previous studies on the relationship between sagittal parameters of cervical spine and Modic changes have found that the larger T1 slope and the smaller and C2-7 lordosis are closely related to the occurrence and development of cervical spine Modic changes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Як зазначають деякі автори, «кіфоз породжує кіфоз» [14]. Крім того, виявлено взаємозв'язок між ступенем кіфотичної деформації та дегенерацією міжхребцевих дисків [15].…”
unclassified